PENGGUNAAN MODEL PEMBELAJARAN ADVANCE ORGANIZER DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM (Lantanida Journal, 2017)
This study aims to improve student learning outcomes , and knowing the students' response to the application of Advance Organizer on Atomic Structure material . Subjects in this study were students of class X SMA Negeri 11 IA3 Banda Aceh , totaling 26 people . This type of research is descriptive qualitative . To find out improving student learning outcomes used about posttest , and the questionnaire used to determine students' response to the learning model Advance Organizer . From the results obtained posttest student learning outcomes at 83.65 ; as well as the students' responses by 96.15 % who expressed delight in learning model Advance Organizer . Based on the results of this study concluded that an increase in student learning outcomes and positive student responses show the learning progress of students with learning model Advance Organizerpada use of the atomic structure of matter.
Keywords: Advance Organizer; Output Learning; Atomic Structure.